(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article aims to study the relationship between psychology and linguistics. The article analyzes the interaction of concepts in the field of psychology and linguistics, their specific features and their similarities. The article shows information based on research in the field of psychology and linguistics and their practical significance. Information based on research in the field of psychology and linguistics and their practical significance will also be shown. The content of the article determines the importance of the connection between psychology and linguistics